2021
DOI: 10.1089/jayao.2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Educational and Vocational Service for Adolescent and Young Adults with Cancer: A Retrospective Review

Abstract: Purpose: A cancer diagnosis and its treatment has the potential to interfere with the ability of adolescent and young adults (AYAs) to remain engaged in education or employment, placing social connectivity, career progression, and financial security at risk. This study aimed at assessing the educational and vocational outcomes of AYAs supported by an Education and Vocational Support Program (EVSP). Methods: Consecutive case files were reviewed of AYAs accessing the EVSP at ONTrac at Peter Mac (January 2014-Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Our findings indicate the need for an intervention involving a multidisciplinary team that can, on the one hand, assist AYAs with cancer in navigating the administrative, legal, financial and psychological issues that can cause severe stress and, on the other hand, can support their social re-entry into everyday life e.g., through educational and financial aid. Several studies point to recognizable benefits of educational and vocational support for AYAs with cancer [ 37 – 39 ]. Among other things, research conducted by Dax et al show that the majority of AYA cancer patients who receive educational and vocational services remain in educational and/or employment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings indicate the need for an intervention involving a multidisciplinary team that can, on the one hand, assist AYAs with cancer in navigating the administrative, legal, financial and psychological issues that can cause severe stress and, on the other hand, can support their social re-entry into everyday life e.g., through educational and financial aid. Several studies point to recognizable benefits of educational and vocational support for AYAs with cancer [ 37 – 39 ]. Among other things, research conducted by Dax et al show that the majority of AYA cancer patients who receive educational and vocational services remain in educational and/or employment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies point to recognizable benefits of educational and vocational support for AYAs with cancer [ 37 – 39 ]. Among other things, research conducted by Dax et al show that the majority of AYA cancer patients who receive educational and vocational services remain in educational and/or employment [ 37 ]. However, further research is still needed to understand and evaluate the support AYAs need to achieve social reintegration after active treatment [ 18 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires using advanced methods to examine multilevel individual and microsystem effects and additional work on the significance of financial health of participants in these instances driving WRGs. Future work should also aim to explore the role of occupational and financial counselors in the care of YAs with cancer (Dax et al, 2020; Leuteritz et al, 2020; Tan et al, 2020).…”
Section: Implications For Occupational Health Nursing Practicementioning
confidence: 99%
“…For AYA brain tumor survivors, assistance in utilizing social resources and peer support may be more useful. It was reported that a vast majority of AYAs remained engaged in education throughout their cancer trajectory with the support of educational support program [ 39 ]. Because AYA patients with brain tumor with cognitive impairment have many unmet needs, establishment of a special educational support program is desired.…”
Section: Introductionmentioning
confidence: 99%